2017
DOI: 10.1200/jco.2017.35.15_suppl.e21670
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine versus aprepitant in the prevention of chemotherapy induced nausea and vomiting (CINV) in breast cancer patients.

Abstract: e21670 Background: Olanzapine has been shown to be a safe and effective agent for the prevention of CINV. This study aims to compare olanzapine with aprepitant in the prevention of CINV. Methods: This study included breast cancer patients receiving doxorubicin 60mg/m2 and cyclophosphamide 600mg/m2 chemotherapy. Female patient; age, ≥ 18; chemotherapy naïve; no nausea/ vomiting in the past 24 hours were included. Patients with seizure disorder, brain metastasis, prior use of antipsychotic agents and hypersensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Three studies reported on olanzapine for the rescue of breakthrough CINV [ 42 44 ]; 22 studies reported on olanzapine in the prophylactic setting [ 45 66 ]. Only seven studies (one reporting on rescue of breakthrough CINV, and six reporting on prophylactic CINV) had no corresponding full-text articles [ 42 , 48 , 53 , 55 , 56 , 60 , 61 ]. One study reported on olanzapine for children [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported on olanzapine for the rescue of breakthrough CINV [ 42 44 ]; 22 studies reported on olanzapine in the prophylactic setting [ 45 66 ]. Only seven studies (one reporting on rescue of breakthrough CINV, and six reporting on prophylactic CINV) had no corresponding full-text articles [ 42 , 48 , 53 , 55 , 56 , 60 , 61 ]. One study reported on olanzapine for children [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the adult prophylactic studies, 15 reported exclusively on HEC patients [ 46 , 49 52 , 55 , 56 , 58 , 60 66 ], three exclusively on MEC patients [ 53 , 57 , 59 ], and three on a patient population that consists of both HEC and MEC patients [ 45 , 47 , 54 ]. Eight studies compared olanzapine to a double-blind placebo-controlled regimen [ 47 , 52 , 59 , 62 66 ] and thirteen used an opened controlled study design—nine studies used a control arm with antiemetics different from the antiemetics in the investigational (olanzapine-containing) arm [ 46 , 49 , 51 , 53 , 55 , 56 , 58 , 60 , 61 ] and four used a control arm with the same antiemetics as in the investigational (olanzapine-containing) arm except for olanzapine [ 45 , 50 , 54 , 57 ]. 17 adult prophylactic studies used 10 mg doses of olanzapine [ 45 , 46 , 49 59 , 61 , 62 , 65 , 66 ], and 3 studies used 5 mg [ 47 , 60 , 63 ]; 1 used a mix of 5 mg and 10 mg [ 64 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%